Vector magnetometry of Fe/Cr/Fe trilayers with biquadratic coupling. (24th April 2017) - Mansell, R; Petit, D; Fernández-Pacheco, A; Lee, J H; Chin, S-L; Lavrijsen, R; Cowburn, R P
Abstract: The magnetic reversal of epitaxial Fe/Cr/Fe trilayer samples grown on GaAs is studied. In wedged samples both long and short period coupling oscillations associated with Ruderman–Kittel–Kasuya–Yosida (RKKY) coupling in Cr are seen in the easy axis saturation fields. By using vector vibrating sample magnetometry and both longitudinal and transverse magneto-optical Kerr effect magnetometry we are able to determine the exact reversal path of both the magnetic layers. Changes in the reversal behavior are seen with sub-monolayer changes of the thickness of the Cr interlayer. The two main reversal paths are described in terms of whether the reversal is dominated by bilinear RKKY coupling, which leads to an antiparallel state at remanence or by biquadratic coupling which leads to a 90 degree alignment of layers at remanence. The changing reversal behaviour is discussed with respect to the possibility of using such systems for multilayer memory applications and, in particular, the limits on the required accuracy of the sample growth.